Environmental education and military education: perspectives on the Pedagogical Political Project (Research, Society and Development, 2022)
The main objective of this article was to carry out an analysis in the Political Pedagogical Project of a military college located in the interior of the Brazilian Amazon on environmental education with methodology under the contribution of the review of the production of knowledge, especially regarding education, school, project pedagogical policy, environmental education, interdisciplinarity, sustainability and militarized teaching. The research is of a documentary and field nature with a qualitative approach, with a case study method. The results are as follows: education is a continuous and permanent process, which must be the responsibility of the school, family and federal agencies, and is legally guaranteed in different laws; the school has different functionalities, it must promote interdisciplinary actions; in the Pedagogical Political Project, it expresses the issue of citizenship and sustainable actions, but that it needs to broaden the actions for this education; Military education also excels in caring for the environment and that environmental education is necessary, as it will greatly contribute to students being able to awaken sensitivity to environmental problems, essentially resulting from anthropic actions.